(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the radial distribution system (RDS), the existence of nonlinear loads causes the generation of harmonic currents, which lead to a lot of problems in the system and equipment, such as electronic equipment is used to control the system due to its effectiveness and accuracy. But these are led to an increase in power losses, equipment will be damaged because of overloads, distortion in voltage and current waveforms. So, the importance of harmonic analysis is increased in the last researches and application for designing and determining its effect in the distribution system. Its benefit appears in finding how much the waveforms for voltage and current are distorted in all the buses in RDS. In this study, we will use the direct approach method to calculate harmonic load flow (HLF) analysis depending on two matrices BIBC and BCBV to determine the relationship between first branch current and bus injection, second branch current with bus voltage. This method is robust and more efficient in solving HLF. It will be applied on IEEE 34 bus system by using a hybrid optimization technique HPOGWO to determine the size for the distributed generated DG. Single, double, and triple units will inject to enhancement voltage profile considering load growth with harmonic sources (HRS) and comparing with the network without HRS.